The good earth - Buck, Pearl S. (Pearl Sydenstricker), 1892-1973 (Buck, Pearl S. (Pearl Sydenstricker), 1892-1973. Good earth trilogy ;, 2012)
Wang Lang, a simple peasant farmer, takes as a wife a battered slave girl who becomes an indomitable, loyal woman. Working the land together, they prosper and increase their holdings, yet Wang eventually betrays his family and neglects the earth he had worshipped.